Application of green silver nano-particles as anti-bacterial and photo-catalytic degradation of azo dye in wastewater - Zainab Haider Ali; Lubna Abdulazeem; Wurood Alwan Kadhim¹; Mazin H. Kzar³; Osamah J. Al-sareji (Scientific Reports)
Abstract Ensuring everyone enjoys healthy lifestyles and well-being at all ages, Progress has been made in increasing access to clean water and sanitation facilities and reducing the spread of epidemics and diseases. The synthesis of nano-particles (NPs) by using microalgae is a new nanobiotechnology due to the use of the biomolecular (corona) of microalgae as a capping and reducing agent for NP creation. This investigation explores the capacity of a distinct indigenous microalgal strain to synthesize silver nano-particles (AgNPs), as well as its effectiveness against multi-drug resistant (MDR) bacteria and its ability to degrade Azo dye (Methyl Red) in wastewater. An extract of Spirulina platensis was obtained from a local source to synthesize silver nano-particles (AgNPs). The synthesized AgNPs were subsequently subjected to characterization utilizing several analytical methods, namely UV-visible spectroscopy, scanning electron microscopy (SEM), X-ray diffraction, and Fourier transform infrared spectroscopy (FTIR analysis). Subsequently, the disc diffusion method assessed their anti-bacterial efficacy against multi-drug resistant (MDR) bacteria and their ability to degrade Azo dye (Methyl Red) in wastewater. The nano-particles produced through biological synthesis exhibited a prominent peak in the UV-visible spectrum at a wavelength of 430 nm. Furthermore, these nano-particles were determined to possess a crystalline nature, with an average size of 28.72 nm and a distinctive star-like shape. The synthesized silver nano-particles (AgNPs) exhibited a dose-dependent anti-bacterial effect against some clinical bacterial isolates as multi-drug resistant (MDR), including Gram− ve bacteria such as Pseudomonas aeruginosa and Escherichia coli, as well as Gram+ ve bacteria like Staphylococcus aureus and Streptococcus pneumoniae. The action can be ascribed to the unique biological and physicochemical features of AgNPs, which facilitate the disruption of bacterial cell membranes. The UV-visible analysis solution after the introduction of AgNPs indicated that the decrease in the absorbance peak of methyl red was attributed to the existence of silver nano-particles. Metal nano-particles can be synthesized using environmentally friendly processes and hold great potential for combating multi-drug resistant bacteria and degrading Azo dyes. Silver nano-particles (AgNPs) are synthesized with an extract derived from the algae Spirulina platensis, which is a sustainable and eco-friendly alternative.